Inside Cover: Electrochemical Oxidation of Small Organic Molecules on Au Nanoparticles with Preferential Surface Orientation (ChemElectroChem 7/2015). Issue 7 (15th July 2015) - Monzó, Javier; Malewski, Yvonne; Vidal‐Iglesias, Francisco J.; Solla‐Gullon, Jose; Rodriguez, Paramaconi
<x xml:space="preserve">Abstract</x> The electrochemical oxidation of small organic molecules in alkaline media is evaluated on gold nanoparticles as a function of the surface structure. Nanoparticles with (111) preferential orientation present higher catalytic activity toward the oxidation of ethanol and glycerol, as discussed by J. Monzó et al. on p. 958.